The Cambrian System in the Arrowie Basin, Flinders Ranges, South Australia. Issue 7 (2nd October 2020) - Jago, J. B.; Gehling, J. G.; Betts, M. J.; Brock, G. A.; Dalgarno, C. R.; García-Bellido, D. C.; Haslett, P. G.; Jacquet, S. M.; Kruse, P. D.; Langsford, N. R.; Mount, T. J.; Paterson, J. R.
Abstract: The lower to ?middle Cambrian rocks (Terreneuvian, Series 2 and possibly Miaolingian) of the Arrowie Basin are exposed superbly in the Flinders Ranges of South Australia. They comprise two major sedimentary packages: a lower carbonate-rich succession (Hawker Group and correlates) and an upper siliciclastic-dominated succession (Billy Creek Formation, Wirrealpa Limestone and Lake Frome Group). These rocks form one of the most complete lower Cambrian (Terreneuvian and Series 2) successions globally. They contain one of the most diverse known early Cambrian biotas in the world, with trilobites, archaeocyaths, bradoriides, brachiopods, some of the earliest known coralomorphs, small shelly fossils, molluscs, hyoliths, acritarchs and trace fossils. Series divisions, based on ranges of shelly fossils and archaeocyath biostratigraphy are currently being established. Ancient reef structures are prominent in several areas. Syndepositional faulting and diapiric activity affected sedimentation in places. The global significance of the region is enhanced by the presence of tuff horizons at some levels, which provide the opportunity to link the biostratigraphic zones with radiometric dates and carbon isotope curves.